How is the activity of shikimate dehydrogenase from the root of Petroselinum crispum (parsley) regulated and which side reactions are catalyzed?. (October 2021) - Hýsková, Veronika; Bělonožníková, Kateřina; Šmeringaiová, Ingrida; Kavan, Daniel; Ingr, Marek; Ryšlavá, Helena
Abstract: Inhibitors of the shikimate pathway are widely used as herbicides, antibiotics, and anti-infectious drugs. However, the regulation of the shikimic pathway is complex, and little is known about the feedback regulation of the shikimate dehydrogenase (SDH, EC 1.1.1.25) in plants. Thus, the aim of this study was to elucidate the kinetic mechanism of SDH purified from the root of Petroselinum crispum (parsley), to determine all possible reaction products and to identify phenylpropanoid compounds that affect its activity. Our results showed that the bisubstrate reaction catalyzed by P. crispum SDH follows a sequential ordered mechanism, except for three dead-end complexes. The main and lateral reactions of SDH were monitored by mass spectrometry, thereby detecting protocatechuic acid as a byproduct. Gallic acid was formed non-enzymatically, whereas quinate was not detected. Several polyphenolic compounds inhibited SDH activity, especially tannic, caffeic and chlorogenic acids, with IC50 0.014 mM, 0.15 mM, and 0.19 mM, respectively. The number of hydroxyl groups influenced their inhibition effect on SDH, and p -coumaric, t -ferulic, sinapic, syringic and salicylic acids were less effective SDH inhibitors. Nevertheless, one branch of the phenylpropanoid pathway may affect SDH activity through feedback regulation. Graphical abstract: Image 1 Highlights: Petroselinum crispum SDH follows an ordered reaction mechanism with three dead-end complexes. Gallic acid and quinate are not direct bypass products of P. crispum root SDH. Tannic acid, chlorogenic acid, and caffeic acid effectively inhibit SDH. P. crispum SDH also forms protocatechuic acid in an irreversible reaction.